Análise morfofuncional dos efeitos do óleo de babaçu não refinado ORBIGNYA PHALERATA MART. (ATTALEA GRASSMANII ZONA): estudo comparativo com azeite de oliva na microcirculação e no fígado - SILVA, Fábio França (2018)
Cardiovascular disease (CVD) is the leading cause of death in Western civilizations. The type of fatty acid which makes up the diet is related to the cardiovascular morbimortality and the formation of atheromas. Populations with high consumption of oils and fats have a higher number of deaths from cardiovascular disease. The Babassu Orbignya phalerata Mart. (Attalea glassmanii Zone) has high oil content in almonds and participates in the diet of several quilombola communities. In the present study, the objective was to comparatively analyze the microcirculatory effects of unrefined babassu oil Orbignya phalerata Mart. (Attalea glassmanii Zone) with Olive Oil in microcirculation and liver of male hamsters of the species Mesocricetus auratus, checking the permeability to macromolecules after ischemia-reperfusion (I / R) without and with topical application of histamine. This is an experimental study, using as model the hamster’s cheek pouch, which was prepared for intravital microscopy. The hamsters were divided into seven groups and orally treated for 14 days, twice a day (at 8 a.m. and 4 p.m.), orally received treatments in the following doses: unrefined babassu oil (BO) 0.02 mL / dose [group BO-2], 0.06 mL / dose [group BO-6], 0.18 mL / dose [BO-18 group], olive oil (OO) 0.02 mL / dose [group OO-2], 0.06 mL / dose [group OO-6], 0.18 mL / dose [OO-18 group], and mineral oil (MO), 0.18 mL / dose [MO-18 group]. The observations were made on the 15th day, on the hamsters’ cheek pouch, being evaluated the increase of vascular permeability induced by I / R without and with histamine application and in the liver the biological material was collected aseptically, then fixed in 10% buffered formalin pH 7.2, macroscopically analysed, processed and embedded in paraffin, cut and stained in hematoxylin / eosin for microscopic analysis. For the microcirculatory analysis, the results showed a significant reduction between the mean values of reperfusion-induced extravasations with and without topical application of histamine was lower in animals treated with unrefined babassu oil at the dose of 0.06mL / dose (BO-6) and 0.18mL / dose (BO-18) than in olive-treated animals at the same doses. A higher dose effect in the BO group (p <0.001) was observed in the decrease of I/R induced macromolecule extravasations without and with topical application of histamine. Histopathological analyzes of the liver did not demonstrate fat deposition in the groups treated with unrefined babassu oil, olive oil and mineral oil at none of the doses. Phytochemical analyzes demonstrated the existence of a chemical component (C31H60NO8) present in unrefined babassu oil and absent in olive oil and the existence of by-products from the degradation of the chemical compound (C37H70NO8) present in unrefined babassu oil and absent in olive oil. The experiments demonstrate the protective effect of unrefined babassu oil on the microcirculatory system without and with topical application of histamine and its superiority with dose effect on olive oil, thus contributing to the insertion of the same in the category of functional food as a vascular protector. The demonstration of a chemical component (C31H60NO8) by the phytochemical analysis present in the BO and absent in the OO arouses interest in the investigation as to the possibility of being this, the chemical compound, responsible for the best protection effect of the membrane permeability observed in the babassu oil in the I / R model, and may in the future be a medicine for the treatment of cardiovascular diseases.